Special article AbdulHamid AbuSulayman civilizational education for transformation - Berghout, Abdul Aziz (Indiana University Press, 2022)
Professor Emeritus Dato’ Dr. AbdulHamid Ahmad AbuSulayman (1936–2021) was born in the city of Mecca, a sacred place in the history of Islam and civilization. Raised in the sociocultural and historical-religious Meccan environment, AbuSulayman showed a sense of ummatic consciousness and civilizational depth as early as his school days in the period 1942–1955. At an early age, he developed the habits of reading and inquisitiveness. These habits escalated in his intellectual journey to produce the sharp critical and analytical mind and personality of AbuSulayman as we came to know it later on. On one occasion, Abu- Sulayman mentioned that he read the book of “the Fall of Al-Andalus,” by Muhamed Abduallah A’nan, in his very young days. Imagine reading such a book and being conscious of the deep crisis of the Islamic civilization from an early age. Such exposures undoubtedly accelerated his intellectual maturation process.